E-commerce in Indonesia: Purchasing Decision of Shopping Online During Pandemic Covid 19 - Chen, James K. C.; Fitri Fadhilla (Archives of Business Research, 2021)
This study aims to identify the effect between trust and convenience towards purchase decisions for e-commerce in Indonesia during pandemic Covid 19. We set variable trust in eight sub-variables, conveniences in five sub-variables, and purchase decisions in four sub-variables. We use regression analysis to describe how trust and convenience affect customers in purchasing services and goods online. We collected the data by online questionnaire from 118 respondents in 2020. This research study shows that trust and convenience significantly affect purchasing the decision for the customer in Indonesia. The findings may be helpful for the online store owner in treating consumers by trust and convenience improvement.